Mental health interventions in schools in low-income and middle-income countries - Fazel, M; Patel, V; Thomas, S; Tol, W (Elsevier, 2014)
Increasing enrolment rates could place schools in a crucial position to support mental health in low-income and middle-income countries. In this Review, we provide evidence for mental health interventions in schools in accordance with a public mental health approach spanning promotion, prevention, and treatment. We identified a systematic review for mental health promotion, and identified further prevention and treatment studies. Present evidence supports schools as places for promotion of positive aspects of mental health using a whole-school approach. Knowledge of effectiveness of prevention and treatment interventions is more widely available for conflict-affected children and adolescents. More evidence is needed to identify the many elements likely to be associated with effective prevention and treatment for children exposed to a range of adversity and types of mental disorders. Dissemination and implementation science is crucial to establish how proven effective interventions could be scaled up and implemented in schools.